1, 8-Cineole: a review of source, biological activities, and application. Issue 10 (3rd October 2021) - Cai, Zi-Min; Peng, Jian-Qing; Chen, Yi; Tao, Ling; Zhang, Yan-Yan; Fu, Ling-Yun; Long, Qing-De; Shen, Xiang-Chun
Abstract: 1, 8-Cineole (also known as eucalyptol) is mostly extracted from the essential oils of plants, which showed extensively pharmacological properties including anti-inflammatory and antioxidant mainly via the regulation on NF-κB and Nrf2, and was used for the treatment of respiratory diseases and cardiovascular, etc . Although various administration routes have been used in the application of 1.8-cineole, few formulations have been developed to improve its stability and bioavailability. This review retrospects the researches on the source, biological activities, mechanisms, and application of 1, 8-cineole since 2000, which provides a view for the further studies on the application and formulations of 1, 8-cineole. Graphical abstract: UF0001